Kinetic study of the dissolution of metallic nickel in sulphuric acid solutions in the presence of different oxidants. (5th August 2016) - Bilczuk, Dario; Olvera, Oscar G.; Asselin, Edouard
Abstract: The dissolution of metallic nickel particles in sulphuric acid solutions has been studied in this work. The effect of temperature, sulphuric acid concentration, and oxidant type has been assessed. In the presence of hydrogen peroxide or dissolved oxygen the dissolution of nickel was fast. A shrinking particle model was used to fit the experimental data and estimate kinetic parameters. The apparent reaction rate constants calculated at 55 °C when dissolved oxygen, ferric sulphate, and hydrogen peroxide were used as oxidants were, respectively, 0.17, 0.02, and 7.13 ms −1 . The dissolution of Ni in the presence of ferric sulphate occurred under surface chemical control, with an activation energy of 82.3 kJ/mol, while in the presence of hydrogen peroxide and dissolved oxygen the reaction seemed to have been mass transfer controlled. The dissolution of Ni in ferric sulphate solutions was also pH sensitive, possibly due to the formation of NiFe2 O4 or NiO that was prevented when sulphuric acid concentration was 1 mol/L. The dissolution rate in ferric sulphate‐free solutions was affected negatively by temperature due to a decrease in O2 solubility.